Symptomatology during previous SARS-CoV-2 infection and serostatus before vaccination influence the immunogenicity of BNT162b2 COVID-19 mRNA vaccine - Nantel, Sabryna; Bourdin, Benoîte; Adams, Kelsey; Carbonneau, Julie; Rabezanahary, Henintsoa; Hamelin, Marie-Ève; McCormack, Deirdre; Savard, Patrice; Longtin, Yves; Cheng, Matthew P.; De Serres, Gaston; Corbeil, Jacques; et al. (Frontiers in Immunology, 2022)
Public health vaccination recommendations for COVID-19 primary series and boosters in previously infected individuals differ worldwide. As infection with SARS-CoV-2 is often asymptomatic, it remains to be determined if vaccine immunogenicity is comparable in all previously infected subjects. This study presents detailed immunological evidence to clarify the requirements for one- or two-dose primary vaccination series for naturally primed individuals. The main objective was to evaluate the immune response to COVID-19 mRNA vaccination to establish the most appropriate vaccination regimen to induce robust immune responses in individuals with prior SARS-CoV-2 infection. The main outcome measure was a functional immunity score (zero to three) before and after vaccination, based on anti-RBD IgG levels, serum capacity to neutralize live virus and IFN-g secretion capacity in response to SARS-CoV-2 peptide pools. One point was attributed for each of these three functional assays with response above the positivity threshold. The immunity score was compared based on subjects’ symptoms at diagnosis and/or serostatus prior to vaccination. None of the naïve participants (n=14) showed a maximal immunity score of three following one dose of vaccine compared to 84% of the previously infected participants (n=55). All recovered individuals who did not have an immunity score of three were seronegative prior to vaccination, and 67% had not reported symptoms resulting from their initial infection. Following one dose of vaccine, their immune responses were comparable to naïve individuals, with significantly weaker responses than individuals who were symptomatic during infection. These results indicate that the absence of symptoms during initial infection and negative serostatus prior to vaccination predict the strength of immune responses to COVID-19 mRNA vaccine. Altogether, these findings highlight the importance of administering the complete two-dose primary regimen and following boosters of mRNA vaccines to individuals who experienced asymptomatic SARS-CoV-2 infection.